Performance comparison of proactive and reactive multicast routing protocols over wireless mesh networks - Azad, Md. Saiful; Anwar, Farhat; Rahman, Md. Arafatur; Hassan Abdalla Hashim, Aisha; Priantoro, Akhmad Unggul; Mohamed, Omer Mahmoud (IJCSNS, 2009)
Multicast routing is a key technology for modern communication networks. It sends a single copy of a message from a source to multiple receivers over a communication link that is shared by the paths to the receivers. This is especially appropriate in wireless environments where bandwidth is scarce and many users are sharing the same wireless channels. In particular, for WMNs, multicast can represent a huge enhancement of the network capacity by taking advantage of links which can be shared by multiple users to receive the same data, which is transmitted only once. To support multicasting, several multicast routing protocols are designed for Internet and Ad hoc networks. However, no specific multicast routing protocol is designed for WMNs. Therefore, the performance comparison of existing multicast routing protocols over wireless mesh networks is essential in order to analyze their behavior and effectiveness. This paper presents the simulation and analysis of the performance of existing proactive and reactive multicast routing protocols over WMNs. Three prominent multicast routing protocols are selected for performance comparison; they are On Demand Multicast Routing Protocol (ODMRP), Multicast Ad hoc On Demand Distance Vector (MAODV) Protocol and Multicast Open Shortest Path First (MOSPF). Among them, MOSPF is a proactive routing protocol while MAODV and ODMRP are reactive multicast routing protocols. MAODV fabricates and maintains a shared multicast tree for each multicast group and ODMRP is a mesh-based approach and uses a forwarding group concept. Our aim is to investigate the relative strength and weaknesses of each protocol.